(untitled) (GAIMS Journal of Medical Sciences, 2023)
Epidermoid cysts / Epidermal inclusion cysts are most common cutaneous cysts and they constitute 18% of eyelid masses. It is frequently seen on the upper eyelid either on the conjunctiva or skin surface. It is seen specifically on the face, neck and trunk and ranges from 1-4 cm in size, more common in males, either in 2nd and 3rd decade. It is usually asymptomatic and mostly presents as a slowly growing painless mass. It is most commonly confused with sebaceous cysts and dermoid cyst but histopathological and radiological examination provide the final diagnosis. Histopathology of the mass reveals a cyst lined by squamous epithelium filled with keratin. Here we present a case report of a 69 years old male, with an epidermoid cyst near medial canthus of left lower eyelid, which was treated surgically. In this case, there is proper clinico-radiological and clinico-pathological correlation which makes it unique.